Good practices performed by nursing to patients undergoing myocardial revascularization (Research, Society and Development, 2022)
The aim of this study is to elucidate through the scientific literature the good nursing practices in myocardial revascularization. The research was descriptive in nature, carried out through a literature review, carried out in the database through the Virtual Health Library (VHL), which covers: LILACS, BDENF, academic Google and SCIELO, through the descriptor: good practices and nursing our acute myocardial infarction. The inclusion criteria were: works published in full, in Portuguese, published in the last 10 years and that have adherence to the theme, in which 21 articles were used to build this study. It is understood that the immediate postoperative period of patients undergoing cardiac surgery takes place in the Intensive Care Unit (ICU), since it is a sector that promotes sufficient resources to care for highly complex patients, such as those who undergo surgery cardiac arrest. Therefore, it was possible to observe the immediate postoperative period of patients undergoing myocardial revascularization, and the importance of systematizing nursing care as a tonic in the effectiveness of care through planning and safe preparation, so that the entire team involved in the process takes an individual and integral approach to the patient.